Aplicação de thidiazuron na cultura do arroz de terras altas irrigado por aspersão na região de Selvíria-MS - Alves, Cleiton José [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Rice is a cereal of large expression in the world all, being able to be exploited in several ecosystems. The Midwest region of Brazil shows whether promising in the expansion of rice crop, being necessary implement techniques to increase rice productivity, such as the use of plant regulators. The objective of the present work was to verify the influence of thidiazuron in rice uplands on the Brazilian Cerrado conditions. The experiment was conducted at the experimental farm belonging to the Faculdade de Engenharia - UNESP - Ilha Solteira Campus, located in Selvíria - MS. The experimental design was a randomized block in a factorial scheme 4x3, consisting of doses (0-0.3-0.6-0.9) and application times (tillering, floral differentiation and booting) of thidiazuron. Were utilized cultivars BRS Esmeralda and IAC 202. The characteristics of plant height and panicle per square meter were not influenced by thidiazuron. The number of spikelet per panicle and fertility of the spikelets of BRS Esmeralda were higher in the tillering stage, using a thidiazuron dose of 0.9 g ha -1 . The weight of 100 grains of the BRS Esmeralda fit to quadratic equation, while in IAC 202 fit to positive linear equation with best time of application during tillering stage. For hectoliter weight of BRS Esmeralda, the results also fit to the quadratic equation, while in IAC 202 significant difference only between times, it is the best booting. The grains productivity of BRS Esmeralda and IAC 202 were fit positive linear with gains of 23.5% and 6.5% compared with the control treatment, respectively. Regarding the milling yield of BRS Esmeralda, the best application time was during the tillering, with reduction in linear values according to increasing doses, however, the IAC 202 presented opposite behavior, with better results for larger doses. The thidiazuron promotes increases in most of characteristics, however, reduces the hectoliter mass and processing quality of ...

O arroz é um cereal de grande expressão no mundo, sendo capaz de ser explorado em diversos ecossistemas. A região Centro-Oeste do Brasil se mostra promissora na expansão da cultura do arroz, sendo necessário implementar técnicas que aumentem a produtividade do arroz, como o uso de reguladores vegetais. Objetivou-se verificar a influência de um regulador vegetal, nas características relacionadas aos componentes biométricos, produtivos e industriais de dois cultivares de arroz de terras altas, BRS Esmeralda e IAC 202, submetidos a aplicação de thidiazuron em épocas e doses, nas condições do Cerrado brasileiro. O experimento foi realizado na Fazenda Experimental pertencente à Faculdade de Engenharia - UNESP - Campus de Ilha Solteira, localizada no município de Selvíria - MS. Utilizou-se um delineamento experimental de blocos casualizados em esquema fatorial 4x3 para cada cultivar, constituído de doses (0-0,3-0,6-0,9 g ha -1 ) de thidiazuron e épocas de aplicação (perfilhamento, diferenciação floral e emborrachamento). As características altura de plantas e panículas por metro quadrado não foram influenciadas pelo thidiazuron. O número de espiguetas por panícula e fertilidade das espiguetas do cultivar BRS Esmeralda foram maiores na fase de perfilhamento, utilizando a dose de 0,9 g ha -1 de thidiazuron. A massa de 100 grãos do BRS Esmeralda se ajustou à equação quadrática, enquanto no IAC 202 houve ajuste à equação linear com melhor época de aplicação durante o perfilhamento. Para massa hectolítrica do BRS Esmeralda, os resultados também se ajustaram à equação quadrática, enquanto que no IAC 202 houve diferença significativa apenas entre as épocas, sendo o emborrachamento a melhor. A produtividade de grãos do BRS Esmeralda e do IAC 202 apresentaram ajuste linear positivo com ganhos de 23,5% e 6,5% respectivamente, em relação à testemunha. Para rendimento de benefício e rendimento de inteiros do...
Keywords: Arroz; Irrigação por aspersores; Reguladores de crescimento; Rice